Paeonol Ameliorates Diabetic Renal Fibrosis Through Promoting the Activation of the Nrf2/ARE Pathway via Up-Regulating Sirt1 - Zhang, Lei; Chen, Zhiquan; Gong, Wenyan; Zou, Yezi; Xu, Futian; Chen, Lihao; Huang, Heqing (Frontiers in Pharmacology, 2018)
Diabetic nephropathy (DN) is rapidly becoming the leading cause of end-stage renal disease worldwide and a major cause of morbidity and mortality in patients of diabetes. The main pathological change of DN is renal fibrosis. Paeonol (PA), a single phenolic compound extracted from the root bark of Cortex Moutan, has been demonstrated to have many potential pharmacological activities. However, the effects of PA on DN have not been fully elucidated. In this study, high glucose (HG)-treated glomerular mesangial cells (GMCs) and streptozotocin (STZ)-induced diabetic mice were analyzed in exploring the potential mechanisms of PA on DN. Results in vitro showed that: (1) PA inhibited high glucose-induced FN and ICAM-1 overexpressions; (2) PA exerted renoprotective effect through activating the Nrf2/ARE pathway; (3) Sirt1 mediated the effects of PA on the activation of Nrf2/ARE pathway. What is more, in accordance with the in vitro results, significant elevated levels of Sirt1, Nrf2 and downstream proteins related to Nrf2 were observed in the kidneys of PA treatment group compared with model group. Taken together, our study shows that PA delays the progression of diabetic renal fibrosis, and the underlying mechanism is probably associated with regulating the Nrf2 pathway. The effect of PA on Nrf2 is at least partially dependent of Sirt1 activation.